Privatization in British Columbia: What the Experts Say Will Happen - Cunningham, Barton; Mitchell, Lari (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1990)
Privatization is being either implemented or investigated in over 100 countries and has become the plan of action for the B.C. government, beginningin the October, 1987. The goal of this Project was to predict the effects of privatization on labour relations in British Columbia. Specifically, it sought to understand how privatization might affect worker stability and wages, the structure and mechanisms for bargaining, the union 's structure and size, and the like. A delphi procédure was carried out in the early fall of 1988 which sought to sample three différent groups — representing union, management, and neutrals (eg., arbitrators). Those targeted were some of the highest ranking labour relations practitioners in British Columbia. The future of B.C. labour relations, based on the delphi prédiction, is one of short term instability for job holders, lower wages, and fragmentation of management's approach to bargaining. There could be increased costs for unions, more militancy, and more difficulties in improving labour relations.